GREEN SUKUK: INSTRUMEN PEMBIAYAAN SEKTOR HIJAU UNTUK MENDUKUNG PEMBANGUNAN BERKELANJUTAN TAHUN 2018 - 2023 - Qur'an, Nurul; Akhmadi, Muhammad Heru (Bisnis-Net, 2025)
This study explores the role of Green Sukuk in supporting Sustainable Development Goals (SDGs) in Indonesia by examining its alignment with Green Eligible Sectors and its impact on sustainability indicators from 2018 to 2023. The research focuses on the suitability of Green Sukuk as an instrument for funding projects that contribute positively to environmental outcomes. It also evaluates how these instruments support long-term strategies for low-carbon emissions and resilience against climatic risks. The research method uses a qualitative approach through literature study and interviews with sources, with data processing involving content analysis and qualitative data analysis. Key findings indicate that Green Sukuk has significantly contributed to reducing greenhouse gas emissions (GHG) and enhancing climate resilience, aligning with 15 Sustainable Development Goals (SDGs).